Modelling and simulation of turbulence in unsteady separated and suddenly-expanded flows - Karantonis, Konstantinos (Cranfield University, 2011)
The scope of this PhD thesis is the simulation of turbulence in time-dependent, separated and suddenly-expanded channel flows. High-resolution and very high-order numerical methods have been employed in the framework of Implicit Large Eddy Simulation (ILES) to elucidate open questions about the physics in flows with sudden expansion. It is well known that the planar sudden expansion (PSE), despite its simple and symmetric geometry it produces a very complex behaviour and a distinctly asymmetric flow pattern ascribed mainly to the Coanda effect. Such flows are encountered in a wide range of practical engineering applications, such as combustion, hydraulic and fluidic devices, air ducts, and mixing equipments. It is of great importance, therefore, to understand the mechanisms that dominate flows with separation and reattachment of the shear layers, as well as flows with regions of strong reversed motion. This thesis has for the first time analysed in detail the turbulent kinetic energy budget (TKEB) for the PSE. This analysis has been extended to examine the influence of Mach number on each individual component of the TKEB. The resulting data can be used as reference for further development of turbulence models capable of accurately resolving the flow behaviour in suddenly-expanded flows. Cont/d.